Tinjauan Yuridis Terhadap Tindak Pidana Korupsi Pada Bank NTT Cabang Surabaya: (Studi Putusan Pengadilan Negeri Kupang Nomor 19/Pid.Sus.Tpk/2021/Pn.Kupang) - George Pascallyus Firman Agung; I Nyoman Gede Sugiartha; I Made Minggu Widyantara (Jurnal Analogi Hukum, 2024)
Corruption is an illegal act involving abuse of authority or trust in order to obtain personal or group benefits, to the detriment of the public interest. Bank NTT as one of the financial institutions has the potential to become a place where corruption crimes occur. The method used is case analysis which involves collecting data from various sources such as news, investigation reports, and related regulations. The results showed that criminal acts of corruption at Bank NTT Surabaya Branch can occur in various ways, such as embezzlement of customer funds, manipulation of financial data, or receipt of bribes from third parties.In overcoming criminal acts of corruption at Bank NTT Surabaya Branch, steps are needed to strengthen internal supervision and stricter law enforcement. Education and training on business ethics and anti-corruption should also be provided to all bank staff.